High force compression mode to shear mode piezoelectric energy harvesting - Crawley, Fergus J. E.; Luo, Zhenhua (IEEE, 2024)
This paper evaluates a novel design of a bridge shear-force structure used to transfer large compressive loads into shear loads on the surface of a piezo disc. The wave/crinkle design can increase the overall number of bridges in a concentric orientation to the circumference with the aim of producing multiple shear force pinch points, changing the shear mode extension path along the piezo discs' axial plane, allowing for tunability, and increasing electrical energy output of a Piezoelectric Energy Harvester (PEH).
Keywords: Piezo; Energy Harvesting; Shear; Compression; Spring Washer; Crinkle Washer; Wave spring